Synthesis, Characterization and in vitro Anticancer Activity of New Quinoline Analogues against Oral Squamous Cell Carcinoma - S., Ugrappa; Fuloria, Neeraj Kumar; Pattabhiraman, Lalitha; Manickam, Ravichandran; Siti Noor Fazliah, Mohd Noor; Maheswaran, Solayappan; Khor, Goot Heah; Mohammad Auwal, Sa'ad; Ajay, Jain; Wu, Yuan Seng *; Venugopal, Balakrishnan; D., Thangeswaran; et al. (Asian Journal of Chemistry, 2023)
Oral squamous cell carcinoma (OSCC) developed from mucosal lining of oral cavity is ranked as 6th most common cancer worldwide. Adverse effects of available anticancer agents intended present work to carry out the synthesis, characterization and evaluation of new quinoline analogues (NQA) against OSCC cell lines. In present study, substituted quinoline (1) was treated with ethyl chloroacetate to offer ester derivative (2), which on treatment with hydrazine hydrate yielded hydrazide derivative (3), which was cyclized into oxadiazole derivative (4) when cyclized with 4-methoxy benzoic acid. Characterization of molecular structures of synthesized NQAs was done based on the FTIR, 1H NMR, 13C NMR and mass spectrometric data. The characterized NQAs were investigated for their anticancer potential. The anticancer studies involved antiproliferation study (IC50 determination) against OSCC cell lines (CAL-27), followed by cell cycle analysis. The results of antiproliferation study of NQAs revealed that among all, NQA 3 exhibited lowest IC50 (3.26 μg/mL). Also, the results of cell cycle analysis of all NQA revealed that all NQAs caused cancer cells arrest in ‘S’ phase. The high anticancer activity of NQA 3 and ability of all the NQAs to cause CAL-27 cells arrest in ‘s’ phase supports their potential application in OSCC treatment. However, the synthesized NQAs must be additionally investigated for the in vivo and clinical studies.